(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The sorption characteristic of Cu (II) from aqueous solution using pre-treated Alternanthera ficoidea leaves as a low cost sorbent has been studied. The prospective of this inexpensive adsorbent was examined for effect of pH, contact time, sorbent dose and initial metal ion concentration in batch experiments. The equilibrium facts were well suited into two most typical isotherm models Freundlich and Langmuir. The Langmuir isotherm model described the sorption isotherm best with good correlation coefficient (R2 = 0.97) as compared to Freundlich isotherm model with (R2=0.95). The correlation coefficient value between 0-1 implies the approving adsorption of copper on adsorbent. The equilibrium time essential for adsorption process was found to be 30 minutes and maximum pH value was determined to be 6. The outcomes indicated that pre-treated A.ficoidea leaves powder has the possibility to be utilized as the cheapest sorbent for the elimination of Cu (II) from aqueous solutions.